Preparation of Unsymmetrical Disulfides from Thioacetates and Thiosulfonates. Issue 41 (24th October 2019) - Delarue Bizzini, Lorenzo; Zwick, Patrick; Mayor, Marcel
Abstract : A method for the transformation of organic thioacetates, a widely used functionality for the preparation of self‐assembled monolayers on gold surfaces, into unsymmetrical disulfides is reported. Disulfides are readily immobilized on gold in contrast to thioacetates, which usually require a deprotection step prior to bonding to the metal surface. The potential of the method for the controlled preparation of unsymmetrical disulfides has been demonstrated with model compounds comprising several thioacetates, which were readily converted into the corresponding unsymmetrical disulfides. Abstract : A versatile method for the preparation of unsymmetrical disulfides from thiosulfonates and thioacetates is described, together with a one‐pot method for the preparation of the required thiosulfonates. The strategy is compatible with a variety of thiosulfonate reagents (R 2 ) and substrates (R 1 ), including multifunctional ones.